The Influence Of Job Mutations And Position Promotions On Employees' Work Spirit At State Savings Bank KCPS Meulaboh - Marini, Tiara; Alisman, Alisman (Economic: Journal Economic and Business, 2023)
This research was conducted at the KCPS Meulaboh State Savings Bank, with the aim of finding out whether job transfers and job promotions had an effect on employee morale. The author's initial hypothesis suspects that there is a positive and significant influence between variable X1 and variable X2 on variable Y. After carrying out further research by distributing questionnaires to 10 employees as respondents, Based on the results of the t test (partial test) for variable X1, the sig value was obtained, namely 0.322>0.05, so in this case it means that variable has no effect on variable Y (Work Morale). For variable X2, the sig value obtained is 0.910>0.05, so in this case it means that variable also has no effect on variable Y (Work Spirit). Based on the results of the F Anova test (simultaneous test), variables X1 and X2 obtained a sig value of 0.543>0.05. So in this case it means that variables X1 and X2 simultaneously (together) have no effect on variable Y.